Modified tibial cortex transverse transport for diabetic foot ulcers with Wagner grade ≥ II: a study of 98 patients - Liu, Junpeng; Yao, Xingchen; Xu, Ziyu; Wu, Yue; Pei, Fuchun; Zhang, Lin; Li, Meng; Shi, Ming; Du, Xinru; Zhao, Hui (Frontiers in Endocrinology, 2024)
Background: Diabetic foot ulcers constitute a substantial healthcare burden on a global scale and present challenges in achieving healing. Our objective was to assess the efficacy of modified tibial cortex transverse transport surgery in managing refractory diabetic foot ulcers.We retrospectively analyzed clinical data from 98 patients suffering from diabetic foot ulcers classified as Wagner grade ≥Ⅱ who were admitted to our medical facility between January 2020 and June 2022. All the patients were treated by modified tibial cortex transverse transport surgery, wherein the osteotomy scope was reduced to two rectangular bone windows measuring 1.5cm × 1.5cm each. Record the patient's general information and ulcer healing time; ulcer area, ankle-brachial index, WIFi classification, and visual analogue scale before and 3 months following the surgical intervention.The average duration of diabetes of 98 patients with diabetic foot ulcer was 20.22±8.02 years, 52 patients had more than one toe gangrene on admission. The postoperative wound healing rate was 95.83% and the average healing time was 53.18 ±20.18 days. The patients showed significant improvement in ankle-brachial index, WIFi classification, and visual analogue scale at 3 months postoperatively compared to preoperatively, with statistically significant differences (P < 0.05). Eight patients experienced complications, and the incidence of complications was 8.16%.Throughout the follow-up period, there were no instances of ulcer recurrence noted.Conclusions: Modified tibial cortex transverse transport surgery demonstrates effectiveness in the management of diabetic foot ulcers by enhancing lower limb microcirculation and facilitating the process of wound healing.